Human adaptations to the last glacial maximum : the solutrean and its neighbors - Schmidt, Isabell; Cascalheira, Joao; Bicho, Nuno Ferreira; Weniger, Gerd-Christian (Cambridge Scholars Publishing, 2019)
The book assembles new insights into humanity's social, cultural and economic developments during the Last Glacial Maximum in Western Europe and adjacent regions. It gathers original, up-to-date research results on the Solutrean techno-complex, reflecting four major fields of research: data from current excavations; analysis of lithic assemblages; new results from studies on climatic conditions and human-environmental interactions; and insights into artistic expressions. New methodological and analytical approaches are applied, providing significant contributions to Paleolithic research beyond.